Tsunami Motion - Othman, Siti Hafizah (Universiti Teknologi Petronas, 2006)
This report is prepared in response to the Final Year Project required for undergraduate students. The project is entitle "Tsunami Motion". Tsunami phenomenon and its impacts on human life have attracted considerable attention after the latest Tsunami on December 2004 hits Indonesia and neighboring ocean countries. Little knowledge is available among civil engineers while they are the ones who should deal with major consequences. The objective of this project is to develop a simple mathematical model in order to determine tsunamis speed and height. A phrase has quoted "Scientists can predict when a tsunami will arrive since the speed of the waves varies with the square root of the water depth". Tsunami waves in the deep ocean can travel at high speeds for long periods of time for distances of thousands of kilometres and lose very little energy in the process. The deeper the water, the greater the speed of tsunami waves will be. The height of a tsunami also depends upon the water depth. A tsunami that is just a meter in height in the deep ocean can grow to tens of meters at the shoreline. Other features which influence the size of a tsunami along the coast are the shoreline and bathymetric configuration, the velocity of the sea floor deformation, the slope of the basin and the efficiency which energy is transferred from the earth's crust to the water column.